Pentingnya Rotasi Partisipasi Kolaboratif Manajerial demi Peningkatan Daya Kompetitif Organisasi di Pasar Global - Laurentius, Lelo Yosep (Bina Nusantara University, 2014)
The background of this research is based on the structure of a company as resource of structural stagnancy on its managerial level. Otherwise, the company structure has to face organizational multidimensional competition in global market. Stagnancy became a problem to an organization if there would be some consequences of working and synergy decreased significantly. The resolution of such stagnancy, especially to those agencies that had good and successful track record, like a manager, can be logically a job rotation. In this case, a manager as an asset of management resource plays an important and strategic position in order to develop a competitive organization in global market nowadays. This research mainly aims to modify the management resources as one of a business strategy to gain successfulness of a company sustainably. This study took quantitative, interpretative, and descriptive approach. The findings of this study indicated that a periodic change in such away like a rotation on the level of managerial collaborative participation which adjusted to the Theory of Contingency by Fiedler can be done in organization system. Besides, it can be held on the level of managers to adapt themselves throughout the global market competition.